A viral insulin-like peptide inhibits IGF-1 receptor phosphorylation and regulates IGF1R gene expression - Chrudinová, Martina; Kirk, Nicholas S; Chuard, Aurelien; Venugopal, Hari; Zhang, Fa; Lubos, Marta; Gelfanov, Vasily; Páníková, Terezie; Žáková, Lenka; Cutone, Julianne; Mojares, Matthew; DiMarchi, Richard; et al. (Molecular metabolism, 2024)
OBJECTIVE: The insulin/IGF superfamily is conserved across vertebrates and invertebrates. Our team has identified five viruses containing genes encoding viral insulin/IGF-1 like peptides (VILPs) closely resembling human insulin and IGF-1. This study aims to characterize the impact of Mandarin fish ranavirus (MFRV) and Lymphocystis disease virus-Sa (LCDV-Sa) VILPs on the insulin/IGF system for the first time. METHODS: We chemically synthesized single chain (sc, IGF-1 like) and double chain (dc, insulin like) forms of MFRV and LCDV-Sa VILPs. Using cell lines overexpressing either human insulin receptor isoform A (IR-A), isoform B (IR-B) or IGF-1 receptor (IGF1R), and AML12 murine hepatocytes, we characterized receptor binding, insulin/IGF signaling. We further characterized the VILPs' effects of proliferation and IGF1R and IR gene expression, and compared them to native ligands. Additionally, we performed insulin tolerance test in CB57BL/6 J mice to examine in vivo effects of VILPs on blood glucose levels. Finally, we employed cryo-electron microscopy (cryoEM) to analyze the structure of scMFRV-VILP in complex with the IGF1R ectodomain. RESULTS: VILPs can bind to human IR and IGF1R, stimulate receptor autophosphorylation and downstream signaling pathways. Notably, scMFRV-VILP exhibited a particularly strong affinity for IGF1R, with a mere 10-fold decrease compared to human IGF-1. At high concentrations, scMFRV-VILP selectively reduced IGF-1 stimulated IGF1R autophosphorylation and Erk phosphorylation (Ras/MAPK pathway), while leaving Akt phosphorylation (PI3K/Akt pathway) unaffected, indicating a potential biased inhibitory function. Prolonged exposure to MFRV-VILP led to a significant decrease in IGF1R gene expression in IGF1R overexpressing cells and AML12 hepatocytes. Furthermore, insulin tolerance test revealed scMFRV-VILP's sustained glucose-lowering effect compared to insulin and IGF-1. Finally, cryo-EM analysis revealed that scMFRV-VILP engages with IGF1R in a manner closely resembling IGF-1 binding, resulting in a highly analogous structure. CONCLUSIONS: This study introduces MFRV and LCDV-Sa VILPs as novel members of the insulin/IGF superfamily. Particularly, scMFRV-VILP exhibits a biased inhibitory effect on IGF1R signaling at high concentrations, selectively inhibiting IGF-1 stimulated IGF1R autophosphorylation and Erk phosphorylation, without affecting Akt phosphorylation. In addition, MFRV-VILP specifically regulates IGF-1R gene expression and IGF1R protein levels without affecting IR. CryoEM analysis confirms that scMFRV-VILP' binding to IGF1R is mirroring the interaction pattern observed with IGF-1. These findings offer valuable insights into IGF1R action and inhibition, suggesting potential applications in development of IGF1R specific inhibitors and advancing long-lasting insulins.
Keywords: Phosphorylation; exprese genu; Receptor, IGF Type 1; Humans; receptor IGF typ 1; Gene Expression; fosforylace; Phosphatidylinositol 3-Kinases; Insulin-Like Growth Factor I; Cryoelectron Microscopy; lidé; zvířata; insulinu podobný růstový faktor I; myši; Mice; protein - isoformy; Protein Isoforms; protoonkogenní proteiny c-akt; Proto-Oncogene Proteins c-akt; Insulin; fosfatidylinositol-3-kinasy; Animals; elektronová kryomikroskopie; inzulin